Povezanost biomehaničkih parametara donjeg ekstremiteta i ukupnog rizika za nastanak dijabetesnog ulkusa stopala - Novaković Bursać, Snježana; Talić, Goran; Tomić, Nataša (Scripta Medica, 2023)
Background/Aim: Preventing lower limb diabetic complications begins with identifying those at risk for diabetic foot ulceration (DFU). DFU development is related to abnormal pattern of plantar pressure distribution caused by alterations in foot rollover process due to loss of foot-ankle muscular strength, impaired range of motion (ROM) and nervous function, as their integrity is needed to enable proper load absorption on plantar surface. Objective of study was to determine correlation between biomechanical parameters of lower limb: ankle and foot muscle strength, ROM at ankle joint (AJ), subtalar joint (SJ) and first metatarsophalangeal joint (I MTP) and overall risk for DFU assessed by IWGDF 2019 Guidance risk stratification system.Methods: A cross-sectional study included 100 diabetic patients, both types. Patients were classified into 4 DFU risk categories applying IWGDF Guidelines 2019 stratification risk system. Function of ten foot and ankle muscles was evaluated by manual muscle testing applying Michigan Diabetic Neuropathy Score system and was expressed by muscle score (MS) on dominant leg. ROM at AJ, SJ and I MTP was measured with a goniometer on dominant leg and was expressed by degree (°).Results: Average MS in specified categories were as follows: Category 0: 9.2; Category 1: 13.9; Category 2: 13.3; Category 3: 15.2 and they were significantly different. Average ROM at AJ in specified categories were as follows: Category 0: 49.3º; Category 1: 48.8º; Category 2: 45.5º; Category 3: 44.6º and they were not significantly different. Average ROM at SJ in specified categories were as follows: Category 0: 37.8º; Category 1: 31.3º; Category 2: 35.0º; Category 3: 28.7º and they were significantly different. Average ROM at I MTP in specified categories were as follows: Category 0: 78.6º; Category 1: 74.4º; Category 2: 65.5º; Category 3: 57.9º and they were significantly different.Conclusions: Risk for DFU ulcer significantly correlates with decreased ankle and foot muscle strength and ROM at SJ and I MTP but does not correlate with ROM at AJ.